Analyzing adhesion in microstructured systems through a robust computational approach. (14th August 2017) - Hoss, Darby J.; Boudouris, Bryan W.; Beaudoin, Stephen P.
Abstract : Analyzing surface forces for myriad geometric structures facilitates the design of properties in interacting interfacial systems. Along these lines, we demonstrate a generalized technique that can be utilized to evaluate the orientation dependence of a particle interacting with multiple finite or semi‐infinite objects. Specifically, the surface element integration technique is modified to account for surface elements of a particle not directly adjacent to the object with which it is interacting; this facilitates the analysis of objects with finite shape and with arbitrary orientations. Furthermore, as a technology‐relevant proof‐of‐concept demonstration, the influence of van der Waals (vdW) forces on the performance and reliability of microstructured systems used for the collection of trace particles is reported. The importance of the location of the particle contact with the microstructure and the independence of vdW forces generated by each microstructure is demonstrated using the developed computational approach. Thus, the methodology presented here can ultimately be utilized for a variety of interfacial forces generated by nontrivial systems with heterogeneous properties in order to provide design motifs in a low‐cost, high‐throughput manner.